Insight into the Antioxidant Activity of Ascorbic Acid-Containing Gelatin Nanoparticles in Simulated Chronic Wound Conditions - María del Carmen Morán; Cristina Porredon; Coloma Gibert (MDPI AG, 2024)
Chronic wounds differ from acute wounds by remaining in the inflammatory phase for a long time. This chronic inflammation confers a high concentration of inflammatory cytokines, proteases, and ROS. Likewise, the pH environment of chronic wounds has been recorded within the range of 7.2-8.9 due to the alkaline by-products of bacterial proliferation. In this work, differences in pH between healthy skin and chronic cutaneous wounds have been used for the design and development of pH-responsive gelatin-based nanoparticles (NPs). Ascorbic acid (AA), as an antioxidant compound that can neutralize reactive oxygen species (ROS), has been the therapeutic model compound included in these NPs. The goal of the present work has been the preparation and characterization (physicochemical and biological properties) of NPs for the effective release of AA under simulated chronic wound conditions. In vitro experiments demonstrated total AA release at pH corresponding to the chronic wounds. The biocompatible character of these gelatin-based NPs based on their hemolytic and cytotoxicity responses has been highlighted under in vitro conditions. The reversible and protective antioxidant properties of the AA-including NPs in erythrocytes and skin cell lines, respectively, have been confirmed to be modulated by the gelatin A gel strength.